A Gender Based Comparison of Civic Responsibility Among University Students in Pakistan (PAKISTAN JOURNAL OF LAW, ANALYSIS AND WISDOM, 2024)
The focus of modern education is to prepare students for civic responsibility. This study examines and compares the perceptions of university students about their level of civic responsibility. A survey method was applied to collect data from the targeted respondents. A total of 154 students of five public sector universities in Khyber Pakhtunkhwa participated in the study based on convenient sampling technique. Results of the study showed that students did not demonstrate desired civic skills and values. Students did not show any concern for civic values. Although, the students accepted that they received good knowledge of civic sense, however, they denied any civic commitment in day to day life. There was no major difference among the students regarding civic development based on gender. However, female students were found to have a slighter higher regard for civic values and commitment than male counterparts. This indicates that there is a need for better civic training of students in Pakistani educational institutions. It is suggested that the curriculum of civics may be revised and more practical knowledge through exploration be emphasized in educational policies for students through interaction in the community rather than traditional lecture based civic orientation.